Human resources management in startups versus mature companies: a pedagogical case study - Alves, Diana Gonçalves Abrantes do Souto (2022)
By looking at companies as a whole, we could assume that Human Resources Management would play a similar role in small firms, such as a startup, to that which they have in more mature companies. However, this is not always true. While some things can, and should work the same, with others it cannot be so, as it will affect the overall performance of the company. This case study goes through the Human Resources Management experience in a multinational startup, and in a mature company. The goal is to understand what are the differences between the two, what is causing those disparities, and what solutions can be implemented in startups, given the resources constraints these companies face. After analysing the experiences of working in a startup and in a larger company, it was possible to conclude that the differences found in the Human Resources Management practices are mainly due to the lack of planning and investment of startups in these practices. However, there are some ways of going around these issues, such as outsourcing HRM or investing on non-monetary forms of compensation.